Max Ernst et Marguerite Duras. Peintre et écrivain de l'exil ? - Fatima SEDDAOUI (Altralang Journal)
ABSTRACT:  Max Ernst and Marguerite Duras are artists who have had an intimate relationship with exile and melancholy. These two themes can be found in both their biographical and artistic backgrounds. On the one hand, Max Ernst, a German painter who spent part of his life in exile, whose paintings are imbued with a melancholy and poetic quality that runs through all his artistic creativity; on the other, Marguerite Duras also experienced exile. In this article, we examine the aspects of exile in the two artistic paths. We will show how the images of Indochina and the United States present themselves on a symbolic level, characterising geographical exile in relation to social exile. To this end, the exile of the 'self' drives them to search for themselves and their fragmented, melancholic unity. Sometimes this is the image of a painting, sometimes it is the image of an evoked narrative, allowing the exile to be inscribed thematically. This article examines the importance and functions of exile in the work of Max Ernst and Marguerite Duras. We analyse the paintings and the writings to affirm that the organisation of the image and the text is oriented towards an artistic creative evolution of exile.